A combined upflow anaerobic sludge bed, aerobic, and anoxic fixed-bed reactor system for removing tetramethylammonium hydroxide and nitrogen from light-emitting diode wastewater. Issue 11 (2nd June 2016) - Lin, Han-Lin; Chen, Sheng-Kun; Huang, Yu-Wen; Chen, Wei-Cheng; Chien, Wei-Cheng; Cheng, Sheng-Shung
ABSTRACT: A laboratory study using a combined upflow anaerobic sludge bed (UASB) and aerobic and anoxic fixed-bed reactor system was undertaken to explore its capability for removing tetramethylammonium hydroxide (TMAH) and nitrogen from light-emitting diode wastewater. When the organic loading rate was maintained at 0.26–0.65 kg TMAH m −3  d −1, the UASB reactor removed 70–100% of TMAH through methanogenesis. When the -N loading rate was maintained at 0.73–1.4 kg -N m −3  d −1, the aerobic reactor oxidized 31–59% of -N to -N through nitritation. When the nitrogen loading rate was maintained at 0.42–0.75 kg N m −3  d −1, the anoxic reactor removed 27–63% of nitrogen through anammox. The performance data of the combined reactor system agreed well with the stoichiometric relationships of methanogenesis, nitritation, and anammox. The batch studies showed that a higher initial TMAH concentration of up to 2520 mg L −1 gave a higher methanogenic activity of up to 16 mL CH4  g −1 VSS d −1 . An increase in the initial TMAH concentration of up to 500 mg L −1 gradually decreased the activity of ammonia-oxidizing bacteria; whereas an increase in the initial TMAH concentration of up to 47 mg L −1 imposed a marked inhibiting effect on the activity of anammox bacteria.